An Analysis of Logistics Efficiency in PT. XYZ Surabaya Branch - Elyn Leevana (iBuss Management, 2015)
Logistic efficiency is an important element in enhancement of company’s competitiveness. Therefore, this research is conducted to investigate factors that influence logistics efficiency using the study case from PT. XYZ. PT. XYZ is a company in distribution industry that distributes palm oil products and other food products from the manufacturer to retail businesses. The researcher will analyze factors that influence logistics efficiency, measured by transportation costs in this research.Research technique utilized in this research is multiple linear regression between several company’s Key Performance Indicators (KPI) which are on time delivery rate, truck capacity utilization rate, order-processing rate and fleet unit utilization rate to transportation costs. The research result shows that the KPI being investigated simultaneously influence transportation costs significantly. However, individually, only truck capacity utilization rate influences transportation costs significantly.Keywords: Logistics efficiency, transportation costs, key performance indicators